Cicero in the Confucius Sinarum Philosophus (1687). Discussion of some emblematic cases between philosophy, religion, and morality - Della Calce, Elisa (Ciceroniana On Line, 2024)
Published in Paris in 1687, the Confucius Sinarum Philosophus represents one of the Jesuit works that, thanks to the use of the Latin language, contributed to spreading Confucian thought across Europe in the XVII century. This paper aims to investigate select examples of quotations and references to Cicero’s works in the Confucius Sinarum Philosophus — Cicero is an author who unsurprisingly was already at the core of the Jesuits’ Ratio studiorum (1599). Moreover, this analysis enables a further exploration of the way in which Cicero’s Latin may represent a trait d’union between Eastern and Western cultures.